Estrategia didáctica "JUEGA APRENDE" para elevar el nivel de aprendizaje del Área Lógico Matemático en los niños y niñas de cinco años de la Institución Educativa Inicial Nº 00206, sector Capironal, Rioja - Cerna Coronel, Celina (2008)
Show it(subj) investigation to once was had as objective to experience didactic strategy HE PLA YS LEARN in order" to lift the learning Mathematical level of the Logical area in the 5- years boys and girls of her Institución Educativa Inicial N; I go into that he justifies himself for his relevance in the country educational specifically in Lógico Matemática´s area that I develop myself in in the initial education level and to have permitted to stimulate in the boys and girls abilities and specific skilfful actions by means of the game that they will serve for them the logical knowledge by means of mathematical and. The theoretic conception that holds the present study was based in Bruners (1983), Vygotskrs (1984) and Dienes's contributions (1971); In addition to sorne studies that served as background of the investigation. Apoyados in the theories mentioned, it carne into question them hypothesis following: Alternative Hypothesis; if Juega experiences didactic strategy herself He learns then will rise significantly the learning Mathematical level of the Logical area in the 5- years boys and grils of her Institución Educativa Inicial N. Void Hypothesis; if Juega experiences didactic strategy herself He learns then will not rise significantly the learning Mathematical level of the Logical area in the 5- years boys and girls of her Institución Educativa Inicial N. The sign was shaped for her 22 boys and gir1s Institución Educativa Inicial N. Right after the analysis and the aftermaths's respective interpretation, the fact that HE PLAYS the didactic strategy's application got confirmed LEARN lnicio's learning level lifted signifia1nlly foreseen Logro in the logical area in the 5- years boys and girls mathematical of her Institución Educativa N.